2020
DOI: 10.1093/molehr/gaaa067
|View full text |Cite
|
Sign up to set email alerts
|

A novel xeno-organoid approach: exploring the crosstalk between human iPSC-derived PGC-like and rat testicular cells

Abstract: Specification of germ cell-like cells from induced pluripotent stem cells (iPSCs) has become a clinically relevant tool for research. Research on initial embryonic processes is often limited by the access to fetal tissue, and in humans the molecular events resulting in primordial germ cell (PGC) specification and sex determination remain to be elucidated. A deeper understanding of the underlying processes is crucial to describe pathomechanisms leading to impaired reproductive function. Several protocols have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, the only previously reported method that allows human primordial germ cell-like cells (hPGCLCs) to develop to later DAZL-positive stages in vitro is to aggregate them with mouse fetal ovarian ( Yamashiro et al, 2018 ) or testicular ( Hwang et al, 2020 ; Kobayashi et al, 2022 ) cells, which mimic the environment of the early gonad. Another study tested aggregation of hPGCLCs with rat neonatal testis cells ( Mall et al, 2020 ), but only showed that the hPGCLCs could survive and did not assess maturation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the only previously reported method that allows human primordial germ cell-like cells (hPGCLCs) to develop to later DAZL-positive stages in vitro is to aggregate them with mouse fetal ovarian ( Yamashiro et al, 2018 ) or testicular ( Hwang et al, 2020 ; Kobayashi et al, 2022 ) cells, which mimic the environment of the early gonad. Another study tested aggregation of hPGCLCs with rat neonatal testis cells ( Mall et al, 2020 ), but only showed that the hPGCLCs could survive and did not assess maturation.…”
Section: Introductionmentioning
confidence: 99%
“… 318 , 319 hPGCLCs are also co-cultured with somatic cells from postnatal rat testes. 320 These somatic cells provide an appropriate niche for hPGCLCs to mature into oogonia or prospermatogonia similar to those of hPGC differentiation in vivo, respectively. Nevertheless, differentiation in vitro from hPGCLCs to mature gametes (ova and spermatozoa) and function testing remain to be explored further.…”
Section: Human Pgclcs Induced Pgc-like Cellsmentioning
confidence: 99%
“…Previous studies focused on the generation of TOs have reported the resuspension of testicular cells directly in Matrigel or agarose [ 6 , 31 , 50 , 51 , 52 ]. In these studies, the time reported for TO formation varies between 2 and 9 days depending on the substrate or culture method and the number of cells used [ 30 , 31 , 32 , 33 , 40 ].…”
Section: Discussionmentioning
confidence: 99%